2021
DOI: 10.1542/peds.2020-042010
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Neonatal Resuscitation Team Training: A Systematic Review

Abstract: CONTEXT: Several neonatal simulation-training programs have been deployed during the last decade, and in a growing number of studies, researchers have investigated the effects of simulation-based team training. This body of evidence remains to be compiled. OBJECTIVE: We performed a systematic review of the effects of simulation-based team training on clinical performance and patient outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…In a neonatal resuscitation setting, teams are usually multidisciplinary, with professionals from different backgrounds often coming together to work for the first time. Team behavior and team communications significantly influence the quality of neonatal resuscitation, and have been implicated in the majority of medical errors, with negative consequences on perinatal morbidity and mortality [ 52 , 53 ]. Simulation-based training can be used to train non-technical skills such as communication, teamwork, and leadership to improve team performance and team coordination [ 8 ].…”
Section: Simulation and Team Training In Neonatal Resuscitationmentioning
confidence: 99%
See 3 more Smart Citations
“…In a neonatal resuscitation setting, teams are usually multidisciplinary, with professionals from different backgrounds often coming together to work for the first time. Team behavior and team communications significantly influence the quality of neonatal resuscitation, and have been implicated in the majority of medical errors, with negative consequences on perinatal morbidity and mortality [ 52 , 53 ]. Simulation-based training can be used to train non-technical skills such as communication, teamwork, and leadership to improve team performance and team coordination [ 8 ].…”
Section: Simulation and Team Training In Neonatal Resuscitationmentioning
confidence: 99%
“…There are few studies evaluating team performance after simulation training in neonatal resuscitation [ 53 , 54 ]. A recent review found significantly improved team performance in simulated re-evaluation 3 and 6 months after simulation training [ 53 ].…”
Section: Simulation and Team Training In Neonatal Resuscitationmentioning
confidence: 99%
See 2 more Smart Citations
“…To increase the use of peer-to-peer support at the bedside, standard resuscitation training is frequently paired with team training [ 47 ]. A systematic review of team training in neonatal emergencies demonstrated that team training improves performance in simulations, and thus may improve performance at the bedside [ 48 ]. One observational analysis of team behavior during clinical newborn resuscitations in the United States illustrated the following three fundamental concepts: communication (i.e., information sharing and inquiry), management (i.e., workload and vigilance), and leadership (i.e., assertion, intentions shared, evaluation of plans) [ 49 ].…”
Section: Clinical Decision Support During Newborn Resuscitationmentioning
confidence: 99%